ANTECEDENCE DAN CONSEQUENCES DARI SATISFACTION WITH RECOVERY TERHADAP FUTURE COMPLAINT INTENTIONS - Franciskus Maya Praba (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2008)
The background of this research is managers need to analyze that customer service failure can arise customer complaint. It must be managed by service recovery to get customer satisfaction. Future complaint intentions has relationship with customer satisfaction. Every company need to investigate which is the compatible perceived justice to applied. The objective of this research is to investigate service recovery effects toward customer satisfaction, especially perceived justice ( interactional, procedural, distributive ) and how justice effects customer satisfaction and future complaint intentions. The design of this research applies to customer Bank BCA in Semarang which is has variants occupation and the questionnaires were spreaded away to 100 respondents by using purposive sampling. The result of this research are interactional justice and procedural justice has more influence on future complaint intentions. Despite, distributive justice and satisfaction with recovery decrease future complaint intentions.Keywords: Antacedence, satisfaction with recovery, future complaint intentions